Investigating the temporal dynamics of auditory processing and selective attention using continous and ecologically valid stimuli : a neural engineering approach - Power, Alan James (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2011)
Auditory Evoked Potentials (AEPs) are a measure of the neural activity in response to auditory stimulation and are used in many clinical and research applications. They are obtained from the electroencephalogram (EEG) by the repeated presentation of discrete auditory stimuli such as tones or noise bursts lasting from Sms to 60ms. EEG activity measured in responses to each individual stimulus is averaged in order to eliminate neural activity not time-locked to the auditory events. The remaining activity is known as an AEP.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.